Of beards and men : the revealing history of facial hair / Christopher Oldstone-Moore. - Oldstone-Moore, Christopher, 1962- (The University of Chicago Press, 2015)
"This fascinating and erudite history of facial hair cracks the masculine hair code, shedding light on the choices men make as they shape the hair on their faces. Oldstone-Moore adeptly lays to rest common misperceptions about beards and vividly illustrates the connection between grooming, identity, culture, and masculinity. To a surprising degree, we find, the history of men is written on their faces"--Amazon.com.